Substitution of Soybean Meal with Indigofera zollingeriana Top Leaf Meal on Egg Quality of Cortunix cortunix japonica - F. Faradillah; R. Mutia; L. Abdullah (Faculty of Animal Science, Bogor Agricultural University, 2015)
This research aimed to study the substitution of soybean meal (SBM) with Indigofera zollingeriana top leaf meal (ILM) in the diet on egg quality of Japanese quails. The experiment used a completely randomized design with five treatments and four replications (ten quails of each replication). The dietary treatment contained five combination of SBM and ILM, R0= diets contained 18% SBM without ILM, R1= diet contained 16.2% SBM and 2.66% ILM, R2= diet contained 14.4% SBM and 5.32% ILM, R3= diet contained 12.6% SBM and 7.98% ILM, R4= diet contained 9% SBM and 13.3% ILM. The results showed that the use of 13.3% ILM (R4) significantly (P<0.05) increased feed consumption, egg weight, yolk colour score, egg cholesterol, and reduced malondialdehyde level. The conclusion of this study was I. zollingeriana top leaf meal could be used as much as 13.3% in the diets. The use of I. zollingeriana top leaf meal could improve the quality of eggs physically and chemically.Key words: eggs quality, Indigofera zollingeriana, soybean meal, quail